Peripheral tuberculous lymphadenitis: Clinical Approach in diagnosis and management and role of surgery - Chowdhury, Md Atiquel Islam (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Abstract not available. J Bangladesh Coll Phys Surg 2023; 41(4): 251-255